From survival instinct to religious belief: Socio-systems analysis in a global context - Nam, Ong Van; Quoc, Nguyen Anh (Edelweiss Applied Science and Technology, 2025)
In the context of globalization, religion, as a complex belief system encompassing social, economic, and political aspects, is undergoing a process of transformation and innovation. This transformation is analyzed from the perspectives of social philosophy and humanistic philosophy to clarify the interaction between religious life and human life. Here, the decline of faith in humanity promotes faith in religion, creating cohesion among people of the same faith, while at the same time causing internal division and conflict. The article focuses on several main issues: the nature of religious faith as opposed to faith in humanity; the division between clergy and believers, and between theists and atheists; the impact of globalization on religious conversion; the role of religion in maintaining social morality and the possibility of its exploitation for political and economic purposes; the trend of conversion and the emergence of new forms of belief. Through analysis, comparison, and especially the inversion method, the article clarifies the relationships between cause and effect, freedom and necessity, ability and need, means and ends, and subject and product in religious life. The research results show that religious conversion in the era of globalization is an inevitable process, reflecting changes in faith, culture, and society. The article proposes a new approach to interreligious dialogue and religious studies from the humanistic and social philosophy methodology, aiming to build a peaceful society and respect differences.